Reciprocal altruism: It's relationship to locus of control and dispositional optimism among Nigerian undergraduates. Issue 2 (4th March 2019) - Afolabi, Olukayode AyoOluwa; Dennis, Uba
Abstract : The study examined locus of control and dispositional optimism influences on reciprocal altruism among Nigerian university undergraduate students. Participants consisted of 253 undergraduate students in their second year of study (males = 151 (60%), females = 102 (40%); mean age = 21.2, SD = 9.10). They completed the Dispositional Optimism Test-Revised (Scheier, Carver, & Bridges, 1994 ), the Altruistic Personality Scale (Rushton, Chrisjohn & Fekken, 1981 ), and the Locus of Control Scale (Rotter, 1966 ). Multiple regression analysis indicated that internal locus of control positively predicted reciprocal altruism; while dispositional optimism did not. Future research should examine other dimensions of optimism such as adaptive utility, comparative and strategic dispositional optimism involved that may provide more insight into the understanding of reciprocal altruism in Nigeria.